Novel causes and consequences of overtraining syndrome: the EROS-DISRUPTORS study - Flavio A. Cadegiani; Claudio E. Kater (BMC, 2019)
Abstract Background Hormonal physiology in athletes, dysfunctional paths leading to overtraining syndrome (OTS), and clinical and biochemical behaviors that are independently modified by the presence of OTS remain unclear. Although multiple markers of OTS have recently been identified, the independent influence of OTS on hormones and metabolism have not been assessed. Hence, the objective of the present study was to uncover the previously unrecognized independent predictors of OTS and understand how OTS independently modifies the behaviors of clinical and biochemical parameters. Methods In a total of 39 athletes (OTS-affected athletes (OTS) = 14 and healthy athletes (ATL) = 25), we performed two clusters of statistical analyses using the full data of the Endocrine and Metabolic Responses on Overtraining Syndrome (EROS) study, in a total of 117 markers. We first used logistic regression to analyze five modifiable parameters (carbohydrate, protein, and overall caloric intake, sleep quality, and concurrent cognitive effort) as potential additional independent risk factors for OTS, and OTS as the outcome. We then used multivariate linear regression to analyze OTS as the independent variable and 38 dependent variables. Training patterns were found to be similar between OTS and ATL, and therefore excessive training was not a risk, and consequently not a predictor, for OTS. Results Each of the three dietary patterns (daily carbohydrate, daily protein, and daily overall calorie intake) were found to be the independent triggers of OTS, while sleeping, social, and training characteristics depended on other factors to induce OTS. Once triggered, OTS independently induced multiple changes, including reductions of cortisol, late growth hormone and adrenocorticotropic hormone responses to stimulations, testosterone-to-estradiol ratio, neutrophils, neutrophil-to-lymphocyte ratio, vigor levels, hydration status, and muscle mass, while increase of tension levels and visceral fat. Conclusions OTS can be independently triggered by eating patterns, regardless of training patterns, while the occurrence of OTS reduced late hormonal responses and the testosterone-to-estradiol ratio, worsened mood, and affected the immunology panel. These novel findings may explain underperformance, which is the key characteristic of OTS.